The facile preparation of self-cleaning fabrics. (18th January 2016) - Chen, Jingyuan; Zhong, Ximing; Lin, Jing; Wyman, Ian; Zhang, Ganwei; Yang, Hui; Wang, Jinben; Wu, Jiazhong; Wu, Xu
Abstract: Self-cleaning surfaces can repel both water and oil, and they have various applications as materials that can protect surfaces against contamination. These surfaces typically exhibit hierarchical surface structures with roughness on both the microscale and the nanoscale, and they are composed of low surface energy components. Such surfaces are normally mechanically weak, and they are prepared using fluorinated solvent-based suspensions consisting of potentially toxic fluorinated compounds. As described in this report, we have demonstrated for the first time, the use of poly(perfluoropropylene oxide) glycol as an environmentally-friendly precursor and a novel acetone-based suspension that only utilized commercially available components for the preparation of self-cleaning cotton fabrics with superhydrophobic and highly oleophobic properties. The coating exhibited outstanding mechanical and chemical durability, and had little influence on the softness or color of the fabric. It is anticipated that these convenient and versatile formulations will facilitate the application of these materials in various fields.